Purrder she wrote - Conte, Cate (Conte, Cate. Cat café mystery., 2018)
It<U+2019>s the grand opening of Daybreak Island<U+2019>s cat café, where customers can get cozy with an assortment of friendly felines<U+2015>and maybe even take one or a few home. Co-owner Maddie James is purring with excitement over her new warm-and-fuzzy venture. . .until she becomes entangled in a petty drama between one of her volunteers, an ardent animal-rights activist, and a wealthy woman who insists on adopting a calico kitty<U+2015>right this instant. The catfight that ensues is bad enough for business. But when the snubbed socialite is found dead with a tell-tale catnip toy on the scene, suspicion lands squarely on Maddie<U+2019>s staffer. Now, with her reputation and her career prospects on the line (to say nothing of her budding romance with a handsome pet groomer) Maddie must do whatever it takes to solve the crime<U+2015>before her nine lives are up.